Role of hystero-laparoscopy in evaluation of infertility: a retrospective observational study - Chouhan, Tulika; Singh, Vinita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Infertility affects 8-10% of couples worldwide. Hystero-laparoscopy offers a dual diagnostic and therapeutic advantage in evaluating infertility, particularly where standard imaging falls short. Objective was to assess the diagnostic value of hystero-laparoscopy in female infertility and identify associated pelvic and intrauterine pathologies. Methods: A retrospective observational study was conducted at AIIMS, Raipur from June 2021 to June 2023, including 140 infertile women (83 with primary and 57 with secondary infertility). Patient records were reviewed for clinical, sonographic, hysteroscopic, and laparoscopic findings, including interventions. Data were analysed using SPSS v22. Results: Mean age was 28.6±4.3 years; mean infertility duration was 4.4±2.2 years. 73.57% of hysteroscopies were normal; uterine septum (15.71%) was the most frequent abnormality. Laparoscopy revealed adhesions (30%), ovarian pathologies (28.57%), and endometriosis (15.71%). Tubal block was noted in 57.85% by HSG. Interventions included adhesiolysis (28.57%), cystectomy (20.71%), and myomectomy (8.57%). Conclusions: Hystero-laparoscopy provides a comprehensive approach to evaluate and treat underlying causes of infertility, especially those undetected by non-invasive imaging.